REKONSTRUKSI SISTEM FISKAL NASIONAL DALAM BINGKAI KONSTITUSI - Ferry Prasetyia (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2011)
There are two main objectives in this research such as identifying the fiscal developmentstage in Indonesia, and reconstruction of national fiscal system in the framework of 1945constitution. The initial foundation that must be built to strengthen the national fiscalsystem is a principle that comes from our basic nation’s cultural such as the principle oftogetherness and kinship. These principles should be supported by the function and basicprinciples of management of state finances such as allocation, distribution, and stabiliza-tion. While the basic principles of state financial management includes transparency, account-ability, efficiency and effectiveness. With the various components are expected to achievea state of self-reliance and fiscal sustainability, which in turn will lead to the ultimate goalof a country that is the welfare of society.Keywords: national fiscal system, welfare and 1945 constitution.